PENGARUH PENERAPAN METODE PROJECT BASED LEARNING (PjBL) PADA MATERI UJI KUALITATIF OBAT - ULUTIAH AAN HIKMAH, HU'UL; NIKMAH, AAN (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2024)
The subject of Pharmaceutical Chemistry is often considered difficult for students to understand. Therefore, an innovative learning method is needed that can connect the material with real-world objects and produce projects in the learning process, one of which is through the implementation of the Project-Based Learning (PjBL) method. This study aims to examine whether the PjBL method can enhance students' science process skills in the topic of "Qualitative Drug Testing." The main objective of this research is to improve students' science process skills through the application of the PjBL method in this subject. The population in this study consisted of 12th-grade students from SMK Negeri 5 Tangerang Selatan in the 2023/2024 academic year, divided into three classes. The research sample included students from the 12th-grade Clinical Pharmacy 1 and 2 classes as the experimental group, while students from the 12th-grade Clinical Pharmacy 3 class served as the control group. Data collection methods included documentation, tests, observations, and questionnaires.Based on test results, the average student score in the control class was 78.24, whereas in the experimental class, it reached 82.39. These findings indicate that implementing the Project-Based Learning method with a Chemoentrepreneurship approach can enhance students' science process skills in the "Qualitative Drug Testing" topic. Additionally, an analysis of student questionnaire responses revealed that this method increases student motivation in learning, fosters collaboration among students, facilitates material comprehension, and boosts confidence in asking questions and responding to peers' opinions. Furthermore, this method encourages active participation in discussions and enhances students' creativity. ABSTRAK Mata pelajaran Kimia Farmasi sering dianggap sulit dipahami oleh siswa. Oleh karena itu, diperlukan metode pembelajaran inovatif yang dapat menghubungkan materi dengan objek nyata dan menghasilkan proyek dalam proses belajar, salah satunya melalui penerapan metode Project Based Learning (PjBL). Penelitian ini bertujuan untuk mengkaji apakah metode PjBL dapat meningkatkan keterampilan proses sains siswa pada materi “Uji Kualitatif Obat.” Adapun tujuan utama penelitian ini adalah meningkatkan keterampilan proses sains siswa melalui penerapan metode PjBL pada materi tersebut. Populasi dalam penelitian ini adalah siswa kelas XII SMK Negeri 5 Tangerang Selatan tahun ajaran 2023/2024 yang terdiri dari tiga kelas. Sampel penelitian siswa kelas XII Farmasi Klinis 1 dan 2 sebagai kelas eksperimen dan siswa kelas XII Farmasi Klinis 3 sebagai kelas kontrol. Metode pengumpulan data dilakukan dengan metode dokumentasi, tes, observasi dan angket. Berdasarkan data hasil tes, rata-rata nilai siswa di kelas kontrol adalah 78,24, sedangkan di kelas eksperimen mencapai 82,39. Hasil ini menunjukkan bahwa penerapan metode Project Based Learning berbasis Chemoentrepreneurship mampu meningkatkan keterampilan proses sains siswa pada materi “Uji Kualitatif Obat.” Selain itu, analisis angket respon siswa menunjukkan bahwa metode ini lebih memotivasi siswa dalam belajar, meningkatkan kerja sama antar siswa, mempermudah pemahaman materi, serta meningkatkan keberanian dalam bertanya dan menanggapi pendapat teman. Selain itu, metode ini juga mendorong keaktifan dalam diskusi serta melatih kreativitas siswa.